PENGARUH RASIO CAR, FDR, BOPO DAN NPF TERHADAP ROA BANK UMUM SYARIAH DI INDONESIA PERIODE 2021-2023 - Ahsan Putra Hafiz; Maulana Hamzah; Seri Jana (MARGIN: Journal of Islamic Banking, 2025)
This study analyzes the effect of CAR, FDR, BOPO, and NPF ratios on the ROA ratio of Islamic Commercial Banks in Indonesia for the period 2021-2023. Using a quantitative method, data were obtained from 30 financial data through annual formats for the period 2021-2023 as published by Bank Indonesia, OJK, and also published on the official website of the sample banks in this study. The partial research results show that the CAR variable has a significant effect on the return on assets (ROA) of Islamic Commercial Banks in Indonesia from 2021 to 2023. The p-value of CAR is 6.80e-07 < 0.05. Meanwhile, the FDR variable does not have a significant effect on the return on assets (ROA) of Islamic Commercial Banks in Indonesia from 2021 to 2023. The p-value of FDR is 0. > 0.05. The BOPO variable has a significant effect on the return on assets (ROA) of Islamic Commercial Banks in Indonesia from 2021 to 2023. The p-value of BOPO is 1.04e-10 < 0.05. And the NPF variable does not have a significant effect on the return on assets (ROA) of Islamic Commercial Banks in Indonesia from 2021 to 2023. The p-value of NPF is 0.3545 > 0.05. The simultaneous regression analysis results show that CAR, FDR, BOPO, and NPF have a significant effect on the ROA of Islamic Commercial Banks, with 89.81% of the ROA variation explained by CAR, FDR, BOPO, and NPF, and the remaining 10.19% explained by other variables not used in this study